MENINGKATKAN HASIL DAN AKTIVITAS MENGGUNAKAN MODEL NHT BERBANTUAN KARTU SOAL TENTANG MOMENTUM DAN IMPULS - Falaqawati, Desty; Silitonga, Haratua Tiur Maria; Hamdani, Hamdani (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2019)
AbstractThis study aims to improve student learning outcomes and activities, using the numbered head together (NHT) model aided by question cards on material momentum and impulses. This research is in the form of a Classroom Action Research (CAR) participant with the CAR model by Kemmis and Mc. Taggart which was conducted in two (2) cycles. Each cycle consist of three (3) stages, namely planning, action and observation, and reflection. Learning outcomes tests and observation sheets of learning activities were given to 33 students in class X MIA 1 of Muhammadiyah 1 Senior High School Pontianak in the 2018/2019 school year. After the NHT model was applied, the student learning outcome scores increased by 0.2 and learning activities increased by 8%. The NHT model can be applied to all subjects and all age levels of students because the NHT model provides opportunities for students to share ideas and consider the most appropriate answers, and can encourage students to improve their spirit of cooperation.Keywords : Learning Activities, Learning Outcomes, Momentum dan Impulses, NHT